Neurology of hereditary metabolic diseases of children - Lyon, Gilles; Adams, Raymond D; Kolodny, Edwin H (McGraw-Hill, 1996)
This unique guide to the diagnosis and management of this difficult group of disorders is organized by age group from the neonate to late childhood. The book\'s eminently readable style explains distinctions between hereditary metabolic diseases and other diseases of the child\'s nervous system. Also included is state-of-the-art coverage of symptomatic treatment, enzyme replacement therapy, and guidelines for the prevention of disease.
Keywords: kojenec; Infant; vnitřní lékařství; Child; vrozené poruchy metabolismu; dítě; neurologie; pediatrie; Metabolism, Inborn Errors; Nervous System Diseases; nemoci nervového systému